Role of the TGF‐β pathway in dedifferentiation of human mature adipocytes. Issue 8 (10th July 2017) - Côté, Julie Anne; Lessard, Julie; Pelletier, Mélissa; Marceau, Simon; Lescelleur, Odette; Fradette, Julie; Tchernof, André
Abstract : Dedifferentiation of adipocytes contributes to the generation of a proliferative cell population that could be useful in cellular therapy or tissue engineering. Adipocytes can dedifferentiate into precursor cells to acquire a fibroblast‐like phenotype using ceiling culture, in which the buoyancy of fat cells is exploited to allow them to adhere to the inner surface of a container. Ceiling culture is usually performed in flasks, which limits the ability to test various culture conditions. Using a new six‐well plate ceiling culture approach, we examined the relevance of TGF‐β signaling during dedifferentiation. Adipose tissue samples from patients undergoing bariatric surgery were digested with collagenase, and cell suspensions were used for ceiling cultures. Using the six‐well plate approach, cells were treated with SB431542 (an inhibitor of TGF‐β receptor ALK5) or human TGF‐β1 during dedifferentiation. Gene expression was measured in these cultures and in whole adipose tissue, the stromal–vascular fraction (SVF), mature adipocytes, and dedifferentiated fat (DFAT) cells. TGF‐β1 and collagen type I alpha 1 (COL1A1) gene expression was significantly higher in DFAT cells compared to whole adipose tissue samples and SVF cells. TGF‐β1, COL1A1, and COL6A3 gene expression was significantly higher at day 12 of dedifferentiation compared to day 0. In the six‐well plate model, treatment with TGF‐β1 or SB431542, respectively, stimulated and inhibited the TGF‐β pathway as shown by increased TGF‐β1, TGF‐β2, COL1A1, and COL6A3 gene expression and decreased expression of TGF‐β1, COL1A1, COL1A2, and COL6A3, respectively. Treatment of DFAT cells with TGF‐β1 increased the phosphorylation level of SMAD 2 and SMAD 3. Thus, a new six‐well plate model for ceiling culture allowed us to demonstrate a role for TGF‐β in modulating collagen gene expression during dedifferentiation of mature adipocytes. Abstract : To gain insights into human adipocyte dedifferentiation, we used a new six‐well plate culture system allowing modulation of the process. We showed a role for TGF‐β in modulating collagen expression during adipocyte dedifferentiation. The six‐well plate model allowed for detailed characterization of the cells regarding a well‐known pathway and could be used to examine other cell programs during dedifferentiation.